ATL. Issue 3 (1st March 2014) - Safra, Tamar; Rogowski, Ori; Muggia, Franco M.
Abstract : Objective: The treatment of recurrent epithelial ovarian cancer (rEOC) remains a major challenge because of the development of platinum resistance. To identify treatment regimens associated with better outcomes in BRCA mutation carriers compared with patients with nonhereditary (NH) disease, we summarized the experience after chemotherapy treatment of rEOC in 1 institution and compared the outcome in BRCA mutation carriers versus NH subsets. Methods: We retrospectively analyzed 256 patient records with rEOC who were treated with second-, third-, and fourth-line treatment with the usual sequential regimens consisting of either pegylated liposomal doxorubicin (PLD), taxanes, gemcitabine, or topotecan (alone or in combination with platinum) between 2002 and 2012 at our institution. The analysis of founder mutations in 8 hotspots was performed. The outcome in BRCA mutation carriers was compared with that of patients with NH disease. Results: BRCA mutation carriers treated with PLD (with or without platinum) or with gemcitabine + platinum had improved progression-free survival (PFS) and a lower risk for disease progression (adjusted for age, line of treatment, and platinum sensitivity) compared with patients with NH disease. By contrast, treatment with taxanes (with or without platinum) or topotecan led to similar PFS in BRCA mutation carriers and in patients with NH disease. Under all treatment regimens, BRCA mutation carriers showed improved overall survival after adjusting for age, line of treatment, and platinum sensitivity. Conclusions: This single-institution experience provides indications of an enhanced benefit in PFS for BRCA mutation carriers compared with patients with NH disease across a number of drug regimens (PLD, platinum, or gemcitabine + platinum) regardless of platinum sensitivity and line of therapy.